The opposing effects of the flavonoids isoquercitrin and sissotrin, isolated from Pterospartum tridentatum, on oral glucose tolerance in rats - Paulo, Alexandra (2015)
The effect of an aqueous extract of Pterospartum tridentatum on the blood glucose levels of normal Wistar rats was investigated in a situation of oral glucose challenge. The extract at 300 mg/kg showed an anti-hyperglycaemic effect in the first 30 min aft